Gender Equality, Disability, and Social Inclusion (GEDSI)-Based Political Education as Social Capital for Female Politicians - Malihah, Elly; Nurbayani, Siti; Komariah, Siti; Sisdiana, Etty; Wirda, Yendri; Utami, Lingga; Munggaran, Rengga Akbar (Universitas Negeri Semarang, 2024)
This study aims to analyze how the contribution of Gender Equality, Disability, and Social Inclusion (GEDSI)-based political education as social capital that can be utilized by female politicians to increase their participation, influence, and role in politics. The research approach used is qualitative with in-depth interview data collection techniques, focus group discussions with research informants involving female politicians involved in the 2024 election contestation. In addition, literature study documents are also a data collection tool that supports research findings. Data analysis was carried out using coding techniques consisting of three stages, open coding, axial coding, and selective coding. The research findings show that the existence of GEDSI political education makes aspects of gender equality, disability inclusion, and social diversity as capital that equips female politicians with the skills to build political strategies, networking skills and overcome structural and cultural barriers in the political system. For female politicians, the implementation of GEDSI political education is used as social capital that distinguishes them from male politicians in advocating policies with a broad perspective in understanding social complexity, thus enabling them to design more responsive and equitable policies. By leveraging the social capital gained from GEDSI education, female politicians can not only strengthen their position on the political stage, but also contribute to creating a more just and representative political governance.